Pengembangan Framework Sistem Informasi Antrian pada Student Service Center Binus University - Reina Reina; Josef Bernadi Gautama (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Queues can be found in all aspects of life, especially in the service industry, including at Binus University in the Student Service Center. Sizeable number of students at certain arrival time, has led to a long queue and this affects student discomfort in waiting. Queue information systems that exist today should bedeveloped further in order to improve the comfort of the user, such as information that is integrated with a student desk, both in seeing a queue number, and knowing the history queue. The research method used is thethree phases of the Software Development Life Cycle methods Problems and Opportunities, System Requirements and System Design. The result of this research is a framework that can be used for queuing system so as to provide the freedom of time and space for the user waiting queue.